Pengembangan Buku Ajar Geografi Pariwisata Berbasis Education For Sustainable Development (ESD) - Nisa, Jakiatin; Windarti, Anissa (Jurnal Sosioteknologi, 2024)
This research aims to assess the feasibility and practicality of developing a tourism geography textbook based on Education for Sustainable Development (ESD) in the Social Sciences Education Study Program at UIN Syarif Hidayatullah Jakarta. This research employed the ADDIE development model from the Robert Maribe Branch for research and development (R&D), a process that encompasses analysis, development, implementation, and evaluation. The trial subjects for textbook products were geography lecturers and students in semesters 3rd and 9th of the 2023-2024 academic year. Data collection techniques included interviews, product validation questionnaires, and lecturer and student response questionnaires. The research instrument comprises interview guidelines, expert review questionnaires, and lecturer and student response questionnaires. The data analysis techniques include (1) preliminary research analysis of interview data; (2) validation questionnaire data analysis; and (3) analysis of lecturer response data and geography. The results of the research show that the feasibility of ESD based on tourism geography textbook materials and media received a score of 3.94 in the feasible category and 4.28 in the very feasible category. The practicalitytest conducted on students and lecturers received an average score of 3.85 and 4.0, respectively, indicating that the tourism geography textbook was considered practical by the students and very practical by the lecturers.